PP022 New Models Are Needed To Optimize The Management Of New Medicines. (2017) - Godman, Brian; Diogene, Eduardo; Fürst, Jurij; Garuoliene, Kristina; Guerra, Augusto; Joppi, Roberta; Malmström, Rickard; Oortwijn, Wija; Selke, Gisbert; Timoney, Angela; Wettermark, Björn
Abstract : INTRODUCTION: Countries are struggling to fund new premium priced medicines with ever increasing prices. In addition, there are substantial savings as medicines lose their patents. This requires coordinated approaches. Models are being developed centering on three pillars: pre-launch including horizon scanning; peri-launch including pricing and reimbursement (P & R)/ risk sharing; and post-launch including assessing effectiveness (1, 2). This will continue to enable access to safe, effective and affordable medicines. METHODS: Desk research of regulatory and other relevant policy documents as well as a thorough and extensive literature search in peer-reviewed databases were conducted. RESULTS: Models to optimize the use of new medicines are being developed. These center on three pillars: pre-launch activities including horizon scanning with a specific focus on unmet needs, drugs expected place in therapy, drugs preliminary budget impact and forecasting (including medicines likely to lose their patents); peri-launch activities including P & R assessment and assessments of risk sharing arrangements; and post-launch activities include assessing the effectiveness and safety of new medicines in routine clinical care (1, 2). Pre-launch activities to agree the number of potential patients for new cancer medicines resulted in hospitals staying within budget (3); and health authorities that had instigated activities pre-launch saw limited excess bleeding with dabigatran (3). Risk-sharing arrangements have increased access to new medicines; however, concerns with their confidential nature and administrative burden (2, 3). Qualitative and/or quantitative approaches are also being developed to better value (new) medicines. There is also growing use of patient level data post launch, for example, studies highlighted concerns with dabigatran prescribing in Spain and anti-obesity medicines in Sweden. Long-term follow-up studies have shown greater effectiveness of ciclosporin versus tacrolimus for transplants despite the rhetoric. CONCLUSIONS: Stakeholders in the healthcare field are working together and developing methods to increase funding for new valued medicines whilst restricting their use where there are concerns to optimize resource use. This will (need to) continue to enable access to safe, (cost-) effective and affordable medicines.